A Bayesian multiple comparison procedure for simply ordered treatment medians. Issue 4 (21st April 2018) - Aghamohammadi, A.
Abstract: This article considers a Bayesian hierarchical model for multiple comparisons in linear models where the population medians satisfy a simple order restriction. Representing the asymmetric Laplace distribution as a scale mixture of normals with an exponential mixing density and a continuous prior restricted to order constraints, a Gibbs sampling algorithm for parameter estimation and simultaneous comparison of treatment medians is proposed. Posterior probabilities of all possible hypotheses on the equality/inequality of treatment medians are estimated using Bayes factors that are computed via the Savage-Dickey density ratios. The performance of the proposed median-based model is investigated in the simulated and real datasets. The results show that the proposed method can outperform the commonly used method that is based on treatment means, when data are from nonnormal distributions.